If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -1) + -1(3x + -5) = 2(3x + -1) + -16 Reorder the terms: 2(-1 + x) + -1(3x + -5) = 2(3x + -1) + -16 (-1 * 2 + x * 2) + -1(3x + -5) = 2(3x + -1) + -16 (-2 + 2x) + -1(3x + -5) = 2(3x + -1) + -16 Reorder the terms: -2 + 2x + -1(-5 + 3x) = 2(3x + -1) + -16 -2 + 2x + (-5 * -1 + 3x * -1) = 2(3x + -1) + -16 -2 + 2x + (5 + -3x) = 2(3x + -1) + -16 Reorder the terms: -2 + 5 + 2x + -3x = 2(3x + -1) + -16 Combine like terms: -2 + 5 = 3 3 + 2x + -3x = 2(3x + -1) + -16 Combine like terms: 2x + -3x = -1x 3 + -1x = 2(3x + -1) + -16 Reorder the terms: 3 + -1x = 2(-1 + 3x) + -16 3 + -1x = (-1 * 2 + 3x * 2) + -16 3 + -1x = (-2 + 6x) + -16 Reorder the terms: 3 + -1x = -2 + -16 + 6x Combine like terms: -2 + -16 = -18 3 + -1x = -18 + 6x Solving 3 + -1x = -18 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 3 + -1x + -6x = -18 + 6x + -6x Combine like terms: -1x + -6x = -7x 3 + -7x = -18 + 6x + -6x Combine like terms: 6x + -6x = 0 3 + -7x = -18 + 0 3 + -7x = -18 Add '-3' to each side of the equation. 3 + -3 + -7x = -18 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = -18 + -3 -7x = -18 + -3 Combine like terms: -18 + -3 = -21 -7x = -21 Divide each side by '-7'. x = 3 Simplifying x = 3
| 15m^2=cm^2 | | X^2=4-4x | | R+t-8r+13t= | | X^2=2-2x | | (7*1.363636364-2)=(-4*1.363636364+13) | | 0.2x+0.5(13-x)=3.2 | | 3(x-y)-2(y-x)= | | (7x-2)=(-4x+13) | | 7x=4(x-8)+3x | | 0.2x+0.5(13-x)=3.8 | | -u^2+8u-16=0 | | 5(a-b)-2(a-b)+8(a-b)= | | (9x+5)=(11x-25) | | 10000*3.12= | | 88=(5+2y)*y | | 3(2b-a)-(2a-b)= | | (X^2+2x+40)=(x^2)-x+190 | | m(x)=x^5-10x^4+25x^3 | | 8(x+y)+3(x+y)= | | 4a+7a=9 | | 4.5x-1.8=3.2x+0.8 | | X^2=3+x | | z+2.6z-5.5=(z-0.3) | | 6(x-y)-3(3x+y)= | | -4.2-6y-4.7-2y=-7y-1.3 | | 4x-12=-48 | | 4(y-7x)-y= | | 5z=18z | | 5z=8z | | 10-(2z-1)=1-3z | | (4x-3)(x-5)=(-11x+1)(3x-2) | | 4x^2-56x+184=0 |